Academic Supervision Cycle Based on Classroom Observation and Professional Feedback at MA Al-Ikhlash Cicalengka - Salman Hasan Ansori; Mulyawan Safwandy Nugraha (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2026)
Although academic supervision contributes substantially to improving instructional quality, empirical studies that integrate classroom observation, professional feedback, and institutional follow-up as a unified supervision cycle in madrasahs remain limited. This study aims to analyze the management of academic supervision through classroom observation and professional feedback at MA Al-Ikhlash Cicalengka. Using a qualitative descriptive case study design, the study involved five informants selected through purposive sampling: the head of madrasah, the Deputy Head for Curriculum, and three supervised teachers. Data were collected through semi-structured interviews, classroom observation data, and document analysis of supervision schedules, instruments, observation notes, and teaching modules. The data were analyzed using Miles, Huberman, and Saldaña’s interactive model, consisting of data condensation, data display, conclusion drawing, and thematic coding. The findings reveal that academic supervision was managed through annual planning, pre-observation communication, instrument-based classroom observation, professional feedback, and follow-up activities. However, its implementation was constrained by limited time, inadequate facilities, uneven feedback delivery, insufficient teacher appreciation, and limited institutional follow-up. The study concludes that academic supervision is more effective in strengthening instructional quality when implemented as an evidence-based professional supervision cycle rather than as an administrative routine. This study contributes to the literature on madrasah-based academic supervision by emphasizing the importance of integrating observation, feedback, and follow-up into a coherent professional development mechanism. The practical implications include the need to establish clearer feedback procedures, strengthen peer supervision, conduct data-based in-house training, and develop teacher appreciation mechanisms. Future research may examine multi-case madrasah contexts, repeated classroom observations, student perspectives, or mixed-methods measurements of changes in teacher practice.